A review of the genus Belciades Kozhanchikov, 1950 (Lepidoptera, Noctuidae, Pantheinae), with descriptions of two new species from China and Thailand. Revision of Pantheinae, contribution II - Behounek, Gottfried; Han, Hui-Lin; Kononenko, Vladimir (Zootaxa, 2011)
The genus Belciades Kozhanchikov, 1950 is reviewed, and its systematic position stated as Pantheinae. Two new species are described, Belciades cyana sp. n. from China, and B. cyanobrunnea sp. n. from China and Thailand. The adult and male and female genitalia of all species are illustrated.